Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s43168-022-00149-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Buteyko breathing technique on asthma severity control among school age children

Abstract: Background Asthma is a complex condition that can impair not only the child’s physical growth but also his optimal functional capacity and performance. Buteyko breathing technique is an exercise designed to regulate the breathing process. This study aimed to evaluate the effect of the Buteyko breathing technique on asthma severity control among school-age children. In Egypt, this technique was applied through five studies, four among adult patients and only one among children. In Mansoura Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This result was supported by Rajendra (2020) and Hassan(2022) who found that comparison of pre and post values of peak expiratory flow rate were done and it shows the significant improvement in peak expiratory flow rate after the intervention of buteyko breathing exercise. (25,20) On the contrary Arora (2019) who mentioned that the there was no statistically significant difference in peak expiratory flow rate and functional capacity suggesting that both conventional physiotherapy and buteyko breathing did not bring about an improvement in peak expiratory flow rate and functional capacity. (26) It was found that there was a positive nonsignificant correlation between age, sex and level of education of children in buteyko ,diaphragmatic and control groups and their peak expiratory flow rate before and after the procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This result was supported by Rajendra (2020) and Hassan(2022) who found that comparison of pre and post values of peak expiratory flow rate were done and it shows the significant improvement in peak expiratory flow rate after the intervention of buteyko breathing exercise. (25,20) On the contrary Arora (2019) who mentioned that the there was no statistically significant difference in peak expiratory flow rate and functional capacity suggesting that both conventional physiotherapy and buteyko breathing did not bring about an improvement in peak expiratory flow rate and functional capacity. (26) It was found that there was a positive nonsignificant correlation between age, sex and level of education of children in buteyko ,diaphragmatic and control groups and their peak expiratory flow rate before and after the procedure.…”
Section: Discussionmentioning
confidence: 98%
“…This finding was supported by Hassan (2022) who reported that there were highly statistically significant differences regarding decrease of means respiration and heart rates of children who received buteyko breathing technique after the procedure. (20) While Rai ,Hembrom, Sharma (2018) who disagreed with these findings and recorded that the heart rate in the post-test was higher than that in the pre-test after practice of buteyko breathing exercise . (21) Concerning the diaphragmatic group, the current study showed that there was a statistically significant difference in the studied children regarding decrease mean of respiratory rate after diaphragmatic breathing exercise and no statically significant regarding heart rate .…”
Section: Discussionmentioning
confidence: 99%
“…The simplicity and accessibility of Buteyko breathing are also noteworthy. Its ease of learning and practice, without the need for specialized equipment, renders it a viable and cost-effective method, particularly beneficial for COPD patients with limited access to comprehensive healthcare resources (31). While BBT demonstrated significant efficacy, it's important to recognize the effectiveness of ACBT in improving dyspnea and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…This might be beneficial in situations when a peak flow meter is unavailable, such as in a prehospital setting, urgent care facility, or doctor's office in such a remote control desert area of Pakistan (Hoesterey et al, 2019). The goal of this study was to evaluate if there was an association between PEFR measures and the amount of time a patient may talk between breaths (speaking time) in ED children patients with an acute asthma exacerbation with their reading comprehension abilities (Hassan, Abusaad, & Mohammed, 2022)…”
Section: Introductionmentioning
confidence: 99%